Best Practise Penerapan Smart Card Modification pada Pengajaran Bahasa Inggris untuk Anak-Anak - Suhartatik Suhartatik; Fusa Prima Dana (IKIP Budi Utomo Malang, 2023)
Best practice in teaching English for young learners by using Smart Card Modification was adjusted to childrens’ cognitive development that focused on the sensory motor phase. This study aimed to enhance English Vocabulary for the students of elementary level under the guidance of Red and White Community Learning Center in Malang Regency. CAR had been designed for two cycles. The statistical analysis determined the mean value 70.2 for students’ outcome and completeness 70 % in Cycle 1, this meant that the success indicator had not yet reached. Later in Cycle 2, the improvement of Smart Card Modification was made to fulfill learning outcome 79.9 and completeness 80%. In conclusion, by using media Smart Card Modification increasedEnglish vocabulary for young learners of Red and White Community Learning Center in Malang Regency.